Systematic Literature Review: Akuntansi Forensik Sebagai Strategi Dalam Upaya Mengatasi Tindak Pindana Korupsi - Ni Made Sintya Surya Dewi; I Gusti Putu Eka Rustiana Dewi (Faculty of Economics and Business, Universitas Warmadewa, 2024)
This article aims to explain the existence of forensic accounting as a strategy in dealing with criminal acts of corruption. This research adopts a Systematic Literature Review approach. The findings from this research confirm that the role of Forensic Accountants is vital in efforts to prevent and reduce acts of corruption. The better the forensic audit is carried out, the more optimal fraud prevention can be. Forensic accounting has a significant impact on supporting the process of eradicating corruption through preventive, detective, and repressive strategies. By applying sophisticated investigative techniques and data analysis, forensic accounting can play a role in uncovering corruption cases, collecting evidence, and compiling relevant expert reports for use in legal processes. However, to face the challenges in fighting corruption, close cooperation between forensic accountants, law enforcement, and other related institutions is crucial. Through this synergy, it is hoped that efforts to eradicate corruption can become more effective and uphold justice.